Physical education and health 1 - Lualhati Fernando Callo (Quezon City : Rex Book Store, Inc., 2023)
"The concepts in this worktext are based on current researches as well as recommendations of local and world-renowned organizations, such as National Association for Sport and Physical Education (NASPE). Moreover, this worktext incorporates differentiated evaluation strategies in order to accommodate the different learning styles of student. It will be valuable learning resources for students who want to become independent, active and lifelong learners.'"
Includes glossary, references, image attribution and index.
English text.